PUBLIC RELATIONS ACTIVITY IN THE FOUNDATION OF TECHNICAL EDUCATION - Zeidan Khalaf, Hutheifa; Hazim Boliss, Nida’a (ALBAHITH ALALAMI, 2022)
Public relations have become vital functions in modern institutions in the complex business world. They play an important role in facilitating the process of communication between the institution and its audiences and achieve mutual understanding between the parties as public relations play this important role based on research and analysis, policy formulation and programming programs and communication with the public. The significance of this research comes from the challenges faced by public relations in state institutions. Misunderstandings and ambiguities still plague most workers in this field, especially in defining the concept, objectives and basic functions of public relations. In addition, there is no clear scientific vision of the significance of the methods used by the Public Relations Department in dealing with the public directly or indirectly. The researcher used the survey method in his study in two theoretical aspects which included the concept of public relations; its objectives and functions and the emergence of the Technical Education Authority; and a practical aspect that included analyzing the results of the questionnaire used by the researcher for research purposes.